2017
DOI: 10.3389/fmicb.2017.01019
|View full text |Cite
|
Sign up to set email alerts
|

The Deep-Sea Microbial Community from the Amazonian Basin Associated with Oil Degradation

Abstract: One consequence of oil production is the possibility of unplanned accidental oil spills; therefore, it is important to evaluate the potential of indigenous microorganisms (both prokaryotes and eukaryotes) from different oceanic basins to degrade oil. The aim of this study was to characterize the microbial response during the biodegradation process of Brazilian crude oil, both with and without the addition of the dispersant Corexit 9500, using deep-sea water samples from the Amazon equatorial margin basins, Foz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…The genus Thermococcus is comprised of sulfur-reducing hyperthermophilic archaea that have a good stress response system (Fukui et al, 2005 ). Studies have demonstrated that anaerobic hydrocarbon degradation is associated with sulfate reduction, fermentative growth, and/or methanogenesis in oil-contaminated marine environments, without requiring exogenous electron acceptors (Orcutt et al, 2010 ; Kotlar et al, 2011 ; Lu et al, 2012 ; Campeão et al, 2017 ). Therefore, the observed co-occurrence patterns of these three taxa with high abundance in the pMENs probably implies potential relevant syntrophic connections between in situ hydrocarbon degradation, sulfur reduction, nitrate reduction, and methane production in the littoral sediment.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Thermococcus is comprised of sulfur-reducing hyperthermophilic archaea that have a good stress response system (Fukui et al, 2005 ). Studies have demonstrated that anaerobic hydrocarbon degradation is associated with sulfate reduction, fermentative growth, and/or methanogenesis in oil-contaminated marine environments, without requiring exogenous electron acceptors (Orcutt et al, 2010 ; Kotlar et al, 2011 ; Lu et al, 2012 ; Campeão et al, 2017 ). Therefore, the observed co-occurrence patterns of these three taxa with high abundance in the pMENs probably implies potential relevant syntrophic connections between in situ hydrocarbon degradation, sulfur reduction, nitrate reduction, and methane production in the littoral sediment.…”
Section: Discussionmentioning
confidence: 99%
“…Seven weeks after the initiation of the oil spill, the dominant Oceanospirillales communities shifted to a community dominated by Cycloclasticus and Colwellia [15][16][17] . Subsequent research showed that some Colwellia responded rapidly in situ 17,18 , and in experiments utilizing controlled additions of oil and dispersed oil 3,17,19 . Other species typically associated with hydrocarbon degradation in the Gulf (i.e., Alcanivorax) were not detected in plume samples 12,15,20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Colwellia aromaticivorans was reported as a novel hydrocarbon-degrading bacterium identified through metagenomic analysis of a microcosm-scale oil exposure experiment (Campeao, Reis et al 2017, Campeao, Swings et al 2019). However, isolation and confirmation of this strain being able to grow on petroleum hydrocarbons has not been performed, only in silico predictions of its metabolic profile have been reported.…”
Section: Dominant Generalists and Phytoplankton-associated Taxamentioning
confidence: 99%